Knowledge Mapping of Green Economy Research: A Bibliometric Analysis - Rigen Mo; Xian-hong Peng; Shao-bu Wang; Justin Zuopeng Zhang (SAGE Open)
With the international community’s commitment to the goals of the Paris Agreement and governments’ implementation of green recovery plans worldwide, the green economy is increasingly recognized as a key strategy to address environmental crises and as a driver of new economic growth. Based on the Web of Science database, this study analyzes 2,106 articles published between 1989 and 2024 and constructs a knowledge graph of the most active institutions and journals in contemporary times. It examines clustering networks and identifies emerging hotspots in recent green economy research. The results indicate that the Chinese Academy of Sciences has the highest number of publications, followed by the University of London and Nanjing University of Aeronautics and Astronautics. The publications predominantly focus on disciplines such as environmental science, environmental studies, and green sustainable science and technology. “Sustainability” is the journal with the most publications, and “Green Economy and Related Concepts: An Overview” is the most cited literature. Rockstrom’s work has played a pivotal role in the evolution of green economy research. The research topics mainly focus on three areas: the necessity of the green economy for human social survival and development, the theoretical framework, models, and pathways of the green economy, and the practice and effectiveness evaluation of green economy initiatives. In the past 5 years, the main keywords discussed include policy, circular economy, and CO2 emissions. These findings provide valuable references for researchers and practitioners engaged in green economy studies.